Post-Activation Performance Enhancement: Save Time With Active Intra-Complex Recovery Intervals - Trybulski, Robert; Makar, Piotr; Alexe, Dan Iulian; Stanciu, Silvius; Piwowar, Rafał; Wilk, Michal; Krzysztofik, Michal (Frontiers in Physiology, 2022)
This study aimed to determine whether the intra-complex active recovery within the strength-power potentiating complex will impact the upper-body post-activation performance enhancement effect and how the magnitude of this effect will change across the upper-body complex training session. Thirteen resistance-trained males [the age, body mass, height, experience in resistance training, and one-repetition maximum (1RM) in bench press were 27 ± 4 years; 92.3 ± 15.4 kg; 182 ± 6 cm; 6.4 ± 2.4 years, and 118 ± 29 kg, respectively) participated in this study. Each participant completed a baseline bench press throw performance assessment at 30% 1RM. Next, five strength-power potentiating complexes consisting of a bench press at 80% 1RM were tested until the average barbell velocity decreased by 10% as a conditioning activity, and 6 min later, a re-test of bench press throw was carried out. During one experimental session during the rest interval inside the complex, they performed swiss ball leg curls, while between the complexes, a plank exercise (PAP-A) was performed. During the second experimental session, participants performed no exercises within the strength-power potentiating complexes and between them (PAP). Under control conditions, participants ran the same protocol (as the PAP condition) without the conditioning activity (CTRL). Friedman’s test showed significant differences in peak (test = 90.634; p < 0.0001; Kendall’s W = 0.410) and average (test = 74.172; p < 0.0001; Kendall’s W = 0.336) barbell velocities during bench press throw. Pairwise comparisons indicated that the peak and average barbell velocities significantly increased in the fourth set [p = 0.022, effect size (ES) = 0.76 and p = 0.013, ES = 0.69, respectively], and the average barbell velocity was also increased in the second set (p = 0.018, ES = 0.77) in comparison to the baseline value during the PAP-A condition. Moreover, the peak barbell velocity was increased in the second (p = 0.008, ES = 0.72) and third (p = 0.019, ES = 0.76) sets compared to the baseline value during the PAP condition. This study showed that body-weight lower-body exercise as an intra-complex active recovery did not impair the upper-body post-activation performance enhancement effect across the complex training session.